PENGARUH RENTANG HARGA DAN MENU TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN “AYAM GEPREK BANGSUR” - Zainarti Zainarti; Demala Sari; Balqis Nurul Zannah; Ayla Rizky Janira (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of price range and menu variety on consumer purchasing decisions at the culinary business “Ayam Geprek Bangsor.” The background of this research lies in the increasing competition within the fast-food industry, making it important for business owners to understand the factors that affect consumer decision-making. A quantitative approach was employed through the distribution of questionnaires to consumers who had previously purchased the product. The data were analyzed using multiple linear regression to examine the effect of each variable. The results show that both price range and menu variety have a positive and significant influence on purchasing decisions, either partially or simultaneously. These findings are expected to serve as a reference for developing marketing strategies and improving product competitiveness